Tuberculosis Coexistence in Pediatric Hodgkin’s Lymphoma: A Tropical Country Experience - Padma, Maneya; Kumar, Nuthan; Munireddy, Jyothi; Kumar, Arun; Gujjal, Pooja Chebbi; Premalata, S. Chennagiri (South Asian Journal of Cancer, 2020)
Introduction Hodgkin’s lymphoma (HL), being one of the common cancers among children, may occasionally masquerade as an infectious illness. Similarly, an underlying infection like tuberculosis (TB) may be missed in cases of HL because of similarity in clinical and radiological features. Here, we present our data of association of HL with histopathologically proven TB lymph node, their clinical presentation, treatment details, and outcome.Materials and Methods A retrospective review of all the cases of HL diagnosed between January 2007 and December 2016 was done. The cases which had an association of TB, based on the histopathology, were reviewed separately.Results A total of 262 children with HL were treated at our institute from January 2007 to December 2016. Of these cases, 42 children had received empirical antitubercular therapy (ATT) (due to suspicion of TB) before presenting to us, and only five cases had histopathologically proven TB lymph node. Ziehl–Neelsen (ZN) stain for acid-fast bacilli (AFB) was positive in the biopsy specimen of all the five cases, proving TB lymph node coexistence with HL. They were treated with six-drug ATT as per the Revised National Tuberculosis Control Program (RNTCP) guidelines along with chemotherapy with adriamycin, bleomycin, vinblastine, and dacarbazine regimen. All the five patients are healthy and disease free until their last follow-up.Conclusion A high-end suspicion for concomitant TB and HL is needed, especially in our country where TB is still rampant. Biopsy with immunohistochemistry and demonstration of AFB can enable a definite diagnosis of both the entities.
Keywords: acid-fast bacillus; coexistence; Hodgkin’s lymphoma; tuberculosis